2010
DOI: 10.1111/j.1752-4598.2010.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

On the vertical distribution of bees in a temperate deciduous forest

Abstract: 1. Despite a growing interest in forest canopy biology, very few studies have examined the vertical distribution of forest bees. In this study, bees were sampled using 12 pairs of flight-intercept traps suspended in the canopy ( ‡15 m) and near the ground (0.5 m) in a bottomland hardwood forest in the southeastern United States.2. In total, 6653 bees from 5 families and 71 species were captured. Augochlora pura (Say) (Halictidae), accounted for over 91% of all bees collected and was over 40 times more abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 25 publications
6
101
3
1
Order By: Relevance
“…Understory species in old-growth deciduous forests may flower before canopy closure in the spring, relying on early season bumble bees, Bombus spp., that can withstand cooler temperatures, or later in the summer, relying on small bees and flies that find strongly-scented floral resources near the forest floor [8,31]. Ulyshen et al [32] reported that the bee assemblage in the understory was distinct from that in the canopy of a temperate deciduous forest. Bees were less abundant and diverse in the understory than in the canopy.…”
Section: Understory Zonementioning
confidence: 99%
“…Understory species in old-growth deciduous forests may flower before canopy closure in the spring, relying on early season bumble bees, Bombus spp., that can withstand cooler temperatures, or later in the summer, relying on small bees and flies that find strongly-scented floral resources near the forest floor [8,31]. Ulyshen et al [32] reported that the bee assemblage in the understory was distinct from that in the canopy of a temperate deciduous forest. Bees were less abundant and diverse in the understory than in the canopy.…”
Section: Understory Zonementioning
confidence: 99%
“…Previous studies performed in temperate forests also showed a vertical stratification in the community composition of hymenopterans (Vance et al 2007;Pucci 2008;Sobek et al 2009;Ulyshen et al 2010Ulyshen et al , 2011. Vance et al (2007) found that, in northeastern temperate forests in Canada, Spheciformes are more common in the canopy than in the understory, suggesting that highly mobile hymenopterans may spend significant amounts of time foraging in this habitat.…”
Section: Discussionmentioning
confidence: 99%
“…and Psenulus spp., predators of sap-sucking insects as aphids, Nitela spp., attacking epiphyte grazers such as barkflies and Spilomena troglodytes, preying on thrips. Previous studies showed that sap-sucking and honeydew producer insects can be abundant in the canopy of temperate forests (Moran & Southwood 1982), turning out to be an important source of non-floral sugar for bees and wasps when only few flowers are available in the understory (Ulyshen et al 2010(Ulyshen et al , 2011. Sampling the arthropod fauna of native and introduced oak species in UK and France, Southwood et al (2005) found that moist higher strata of broadleaf forests can host a very abundant and diverse epiphyte fauna, including Psocoptera and Thysanoptera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations